2022
DOI: 10.1002/ptr.7545
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides of Brassica rapa L. attenuate tumor growth via shifting macrophages to M1‐like phenotype

Abstract: Macrophages are the major tumor‐infiltrating leukocytes, and tumor‐associated macrophages (TAM) play a critical role in cancer‐related inflammation since they show alternative polarization to M1 (tumor‐inhibited macrophages) or M2 (tumor‐promoted macrophages) phenotype. Brassica rapa L. (B. rapa) has been clinically proven to have anti‐tumor and immunity‐enhancing activity, and the polysaccharides of B. rapa (BRP) have been reported to have an immunoregulatory effect on macrophages. In this study, we focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The expression of FAP was also strongly positively correlated with the expression of CD206 and CD163, markers of M2‐type macrophages, based on the TCGA dataset (Figure 5F,G, p < 0.001, Pearson's r test). In previous studies, CD68, CD11b, and CD14 are often used to define M0‐type macrophages, while CD206, CD163, and ARG1 are often used to define M2‐type macrophages 17–19 . To better define the cell population, in this study, we used CD68 and CD11b to define M0 macrophages, and CD206 and CD163 to define M2‐type macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of FAP was also strongly positively correlated with the expression of CD206 and CD163, markers of M2‐type macrophages, based on the TCGA dataset (Figure 5F,G, p < 0.001, Pearson's r test). In previous studies, CD68, CD11b, and CD14 are often used to define M0‐type macrophages, while CD206, CD163, and ARG1 are often used to define M2‐type macrophages 17–19 . To better define the cell population, in this study, we used CD68 and CD11b to define M0 macrophages, and CD206 and CD163 to define M2‐type macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, CD68, CD11b, and CD14 are often used to define M0‐type macrophages, while CD206, CD163, and ARG1 are often used to define M2‐type macrophages. 17 , 18 , 19 To better define the cell population, in this study, we used CD68 and CD11b to define M0 macrophages, and CD206 and CD163 to define M2‐type macrophages. The results of flow cytometry showed that the expression levels of CD68 and CD11b in U937 monocytes were significantly increased under the induction of PMA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the whole, although YPS could not directly limit M1 polarization during the stimulation process of AA, it indeed had a certain impact on the polarization trend of RAW264.7 cells, thereby affecting cell function and homeostasis. According to literature, M1 polarization was stimulated by various polysaccharides including Poria cocos Polysaccharide PCP-1C, Dendrobium officinale polysaccharide, polysaccharides of Brassica rapa L.,Apple polysaccharide,Astragalus polysaccharide RAP, Tremella fuciformis polysaccharide (Guo et al, 2022;Hu et al, 2023;Sun et al, 2020;Wang et al, 2022a;Wei et al, 2019;Xie et al, 2023) . However, it is also reported that polysaccharide from Large Yellow Tea (LYP-S3) and Laminaria japonica could promote the M2 polarization of macrophages (Li et al, 2022b;Wang et al, 2022b) .…”
Section: The Effects Of Yam Polysaccharidesmentioning
confidence: 99%